Film Thickness and Friction Relationship in Grease Lubricated Rough Contacts - Gonçalves, David (2020)
The relationship between the film generation and the coefficient of friction in grease lubricated contacts was investigated. Ball-on-disc tests were performed under different operating conditions: entrainment speed, lubricant temperature and surface roughness. The tests were performed with fully formulated greases and their base oils. The greases were formulated with different thickener types and also different base oils natures and viscosities. Film thickness measurements were performed in ball-on-glass disc tests, and Stribeck curves were measured in ball-on-steel disc tests with discs of different roughness. The role of the thickener and the base oil nature/viscosity on the film thickness and coefficient of friction was addressed and the greases’ performance was compared based on their formulation.